2010
DOI: 10.1259/bjr/61140265
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings of uncommon non-hepatocyte origin primary liver tumours with pathological correlation

Abstract: ABSTRACT. The objective of this article was to illustrate the MRI findings of uncommon non-hepatocyte origin primary liver tumours, correlate them with the pathological features and discuss differential diagnoses. In conclusion, the MRI findings of uncommon benign and malignant non-hepatocyte-origin primary liver tumours vary. Awareness of characteristic MRI features can aid differential diagnosis and prevent unnecessary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…All eleven published cases demonstrated arterial phase enhancement (7, 10-13, 15, 17, 18), six continued to show hyperenhancement in portal venous and delayed phases (11,17,18), whereas three were hypointense (7,10,13) and two were isointense (12,15). These findings were overall consistent with our case series with all three cases demonstrating arterial phase hyperenhancement that persisted on portal venous or delayed phase imaging.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All eleven published cases demonstrated arterial phase enhancement (7, 10-13, 15, 17, 18), six continued to show hyperenhancement in portal venous and delayed phases (11,17,18), whereas three were hypointense (7,10,13) and two were isointense (12,15). These findings were overall consistent with our case series with all three cases demonstrating arterial phase hyperenhancement that persisted on portal venous or delayed phase imaging.…”
Section: Discussionsupporting
confidence: 87%
“…Given the confusion with BDA nomenclature in the published literature, particularly with biliary hamartomas (Von Meyenberg Complexes), articles were included if the described histologic description of BDA was specified (i.e., numerous and small ducts interspersed with fibrous stroma) (8). Our search identified 10 studies with 13 cases in total (7,(10)(11)(12)(13)(14)(15)(16)(17)(18). These results are summarized in the Table, including imaging findings from the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Adachi et al [2] 10 64/M Left lobe/4.0 Unknown + CT: heterogeneous density Fever Lateral segmentectomy Ortiz et al [11] 11 19/F Left lobe/5.5 Negative + CT: Hypovascular Abdominal fullness Left lobectomy Szekely et al [10] 12 60/M Unknown 6.0 Unknown (non-B, non-C) [7] 14 61/M S6/2.2 Unknown + Sonography: hypoechoic CT: low density w/o enhancement MR: T1 slightly hypointensity, T2 hyperintensity, progressive enhancement in periphery of the lesion…”
Section: Incidental Finding Resectionmentioning
confidence: 99%
“…Lymphoepithelioma-like carcinoma (LELC) is a tumor with morphologic features similar to those of undifferentiated nasopharyngeal carcinoma that occurs outside the nasopharynx and is associated with Epstein-Barr virus (EBV) infection. In the liver, this type of tumor is extremely rare, and only 23 cases of lymphoepitheliomalike cholangiocarcinoma have been described in reports focused on histologic and immunohistochemical analyses [1][2][3][4][5][6][7][8][9][10][11][12] . A recent study that reported seven female cases of EBV-associated lymphoepithelioma-like cholangiocarcinoma demonstrated molecular genetic pathology, including frequent DNA hypermethylation [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Given the confusion with BDA nomenclature in the published literature, particularly with biliary hamartomas (Von Meyenberg Complexes), articles were included if the described histologic description of BDA was specified (i.e., numerous and small ducts interspersed with fibrous stroma) (8). Our search identified 10 studies with 13 cases in total (7,(10)(11)(12)(13)(14)(15)(16)(17)(18). These results are summarized in the Table, including imaging findings from the present study.…”
Section: Methodsmentioning
confidence: 99%